Prognosis of Chronic Rhinosinusitis With Nasal Polyps Using Preoperative Eosinophil/Basophil Levels and Treatment Compliance. Issue 5 (September 2018) - Guo, Michael; Alasousi, Fahad; Okpaleke, Christopher; Habib, Al-Rahim; Javer, Amin
Background: Patients with chronic rhinosinusitis with nasal polyps (CRSwNP) have a high risk of disease recurrence and revision surgery. The ability to predict a polyp recurrence in this patient population is critical in order to provide adequately tailored postoperative management. Objective: We aim to explore the role of appropriate postoperative care in the prognosis of CRSwNP patients in relation to preoperative eosinophil and basophils levels. Methods: This was a retrospective case series; data were collected for 102 CRSwNP patients over a period of 15 months after surgery. Baseline eosinophil and basophil levels were compared between patients with and without polyp recurrences. The analysis was then stratified based on clinical diagnosis, comorbidities (atopy, asthma, and aspirin allergy), a single versus multiple episodes of sinonasal polyp recurrences, and medication adherence. Results: Of the 102 included patients, 65 (63.7%) of the patients experienced no recurrences, 26 (25.5%) experienced a single episode of recurrence, and 11 (10.8%) experienced multiple recurrences. Mean baseline eosinophil count and percentage of total white blood cells were significantly higher in the multiple recurrences group (0.70 × 10 9 /L and 10%) compared with the no recurrences group (0.36 × 10 9 /L and 5%). Adherence to prescribed medical therapy prior to the first episode of recurrence was significantly lower for the single exacerbations group (42.3%) than the multiple recurrences group (88.9%). Conclusions: Patients with multiple recurrences of nasal polyps had significantly higher baseline eosinophil counts and significantly higher medication adherence compared to single exacerbations of nasal polyps. Single exacerbations may not reflect true failures of surgery but rather a failure of postoperative medical care. Basophil levels were inadequate to predict polyp recurrence rates.